EU fiscal federalism : past, present, future - Hinarejos, Alicia <<[HerausgeberIn]>>; Schütze, Robert <<[HerausgeberIn]>> (Oxford University Press, 2023)
"Fiscal federalism refers to the division or distribution of fiscal powers between different levels of government. In the context of the European Union, it provides a framework to explore the foundations and evolution of the Union's (limited) fiscal powers across different areas of EU competence. The European Union is often seen as a legislative giant on clay feet, and one of the principal reasons for this feebleness is the lack of a significant fiscal capacity at the Union level. In the long term, the current state of affairs may prove itself unsustainable, in light of the need to ensure the macroeconomic stability of the euro area and of calls to transfer further re-distributional tasks to the European level. The ongoing - and highly topical - discussion on greater fiscal union has taken place mostly within the realm of the EU's Economic and Monetary Union (EMU). This discussion should, however, be seen as a part of a bigger picture and in historical perspective; one that also takes into account the role of fiscal matters in other areas of EU competence"--